Angiotensin-converting enzyme gene (I/D) polymorphism in association with diabetic nephropathy - Hasan, Taner; Trajkovska, Ivana; Balovski, Marjan; Minova Nedeska, Natasha; Volkanovska Ilijevska, Cvetanka; Doneva, Daniela; Pakovski, Kiril; Josifovska, Slavica; Panov, Sasho (SHMSHM - AAMD, 2018)
Polymorphisms in the Angiotensin-converting enzyme (ACE) gene have been associated with development of diabetic nephropathy (DN), a major microvascular complication of the type 2 diabetes mellitus (T2DM). Since the genetic predisposition plays an important role in development of DN in patients with T2DM, genetic testing might largely contribute to better assessment of the risk of DN in such patients. The aim of this study is to investigate the association of the ACE gene I/D polymorphism with DN in T2DM patients. The study is designed as a casecontrol genetic association study. The samples from 88 patients with T2DM were analyzed, including 57 patients with DN and 31 without DN. The study includes also 26 healthy controls. The demographic, clinical and laboratory data are analyzed in addition to the genetic profiling of the patients for the ACE gene. Genotyping of the ACE gene I/D polymorphism resulted in determination of the patient’s genotype: D/D, I/D or I/I. The results revealed a statistically significant association of genotypes D/D and I/D with the occurrence of nephropathy compared to the I/I genotype. In the group of patients with T2DM, the carriers of the D/D or I/D genotypes have 6.46 folds higher odds and 1.7 folds higher relative risk for developing nephropathy than the carriers of I/I genotype. The results confirmed the correlation of the genetic polymorphism and the development of the DN in patients with T2DM indicating its potential predictive use in terms of the clinical follow-up, treatment selection and prognosis of DN.
Keywords: ACE gene; nephropathy; polymorphisms; type 2 diabetes